Spiritual Emotional Freedom Technique and Progressive Muscle Relaxation to Reduce Fatigue in Hemodialysis Patients - Ida Rosdiana; Yanti Cahyati; Asep Riyana (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Fatigue represents a common and debilitating complaint in individuals undergoing dialysis, with substantial implications for quality of life and overall well-being. This study investigated the effect of combining Spiritual Emotional Freedom Technique (SEFT) therapy with Progressive Muscle Relaxation (PMR) exercises on fatigue levels among hemodialysis patients at Dr. Soekardjo Tasikmalaya Regional General Hospital. Methods: A quasi-experimental pretest-posttest design was employed to evaluate the effects of a combined intervention involving Spiritual Emotional Freedom Technique (SEFT) and Progressive Muscle Relaxation (PMR) on fatigue levels. The study included 49 hemodialysis patients who fulfilled the established inclusion criteria. Fatigue intensity was assessed using the Fatigue Severity Scale (FSS), and statistical analysis was performed with a paired t-test, with significance determined at p < 0.001. Data collection took place between July and September 2022. Results: The mean fatigue score significantly decreased from 51.8 ± 10.0 before the intervention to 17.5 ± 5.2 after the intervention (p < 0.001). Conclusion: SEFT therapy combined with PMR exercises effectively reduces fatigue in hemodialysis patients. Nurses are encouraged to incorporate these techniques into comprehensive self-care interventions for hemodialysis patients. The study was constrained by being conducted at a single institution and by the inclusion of a relatively limited number of participants, factors that may restrict the broader applicability of the results. Future research with a larger, multi-center sample is recommended.